Subjective cognitive decline is related to CSF biomarkers of AD in patients with MCI - Wolfsgruber, Steffen; Frölich, Lutz; Schröder, Johannes (Neurology, 2015)
Objective: To test whether, in individuals with mild cognitive impairment (MCI), different measures of subjective cognitive decline (SCD) in the memory domain predict abnormal CSF biomarkers of Alzheimer disease (AD). Methods: We analyzed the multicenter baseline (cross-sectional) data of 245 patients with MCI. SCD was measured quantitatively with the Subjective Memory Decline Scale (SMDS) and qualitatively by assessing particular concerns associated with self-experienced worsening of memory. Logistic regression models were used to examine associations between SCD and abnormal CSF biomarkers, taking into account objective memory impairment, depressive symptoms, and education as covariates. Results: Abnormal CSF β-amyloid 1-42 (Aβ42) and more depressive symptoms were associated with higher SMDS scores and with the report of memory concerns. Risk of abnormal CSF Aβ42 increased by an estimated 57% for a 1-SD increase in SMDS scores and was doubled in patients who had SMDS scores >4 or who reported memory concerns, respectively. In addition, both SCD measures predicted risk of having a biomarker signature indicative of prodromal AD defined as presence of low CSF Aβ42 together with either high CSF tau or CSF phosphorylated tau 181 levels. Conclusions: In MCI, specific aspects of SCD severity and quality are related to CSF biomarkers indicative of AD. This extends findings in pre-MCI samples and calls for an improved operational assessment of SCD in MCI. This might be useful for sample enrichment strategies for increased likelihood of AD pathology.